Analisis kekuatan pembebanan frame mesin press hidrolik kapasitas 3 ton - Ghifari, Muhammad Aqshal; Prihastuty, Endang; Tohasan, Achmad (Universitas Majalengka, 2024)
This study examines the safety and stress factors to determine the maximum dynamic load that can be supported by the press machine frame. Dynamic loads occur due to the working mechanism of the press machine that presses the bearing. Stress analysis test simulation using the Solidwork 2020 computer program with the finite element method in the simulation test of the hydraulic press machine frame material structure with dynamic load treatment. The frame design model uses U-profile iron material UMP 50 with a thickness of 3-5mm with dimensions of 50 mm x 38 mm. The simulated variable load is 3000 kg. The simulation results show the yield strength of the material = 521.927 N / m² (Mpa) and the stress, displacement, strain values ​​at a load of 3000 kg = simulation Stress = 620.422 N / m² (Mpa), Displacement = 1.232mm, Strain = 0.001. The von Mises stress value is 29,500 N = 620.422N; 521.927 N = 1.88. The simulation results show that the hydraulic press machine frame design has a safety factor of 0.001 and can withstand dynamic loads of up to 3000 kg.